Career Aspirations Of R&D Professionals In Malaysian Government Research Institutes - Ramly, Efizah Sofiah (2009)

(untitled)
One of the strategic mechanisms for human resource development (HRD) practitioners in developing career development program for research and development (R&D) professionals is by managing their career aspirations (Petroni, 2000). It is believed that career aspiration is one of the internal needs for motivating R&D professionals to succeed in their careers. This study therefore would contribute insights into the management of R&D professionals’ careers, where their internal needs could be fulfilled through their aspirations. There are three factors that had been recognized to have influenced the R&D professionals’ career aspirations in Malaysian Government Research Institutes (GRI), namely, self-efficacy, organizational socialization and continuous improvement (CI) practices. These factors were selected based on the components of Social Cognitive Career Theory (SCCT) developed by Lent, Brown and Hackett (1994). The objectives of this study were to determine the levels of career aspiration, self-efficacy, organizational socialization and CI practices of R&D professionals in GRI, to determine the relationship between each factor and their career aspirations, and to determine the contribution of each factor to their career aspirations. The design of this study was a descriptive correlational research where it was conducted through a quantitative research method on 158 R&D professionals. The respondents were gathered through a purposive sampling procedure and the response rate was 69.30%. The data for this study were collected using a set of questionnaire which consists of simplified version of Schein’s Career Anchor Inventory (Igbaria, Kassicieh, & Silver, 1999), the General Self-efficacy scales (Schwarzer & Jerusalem, 1995), the Organizational Socialization Inventory (Taormina, 1994), and the CI Cpabilities Survey (Jorgensen, Boer, & Laugen (2006). The data were then analyzed using descriptive statistics to see the distributions of the respondents based on age, gender, marital status, educational attainment, and working experience. Pearson Product-Moment correlation analysis was also conducted to explain the relationship among the variables and multiple linear regressions analysis was conducted to predict the contribution of self-efficacy, organizational socialization, CI practices to the R&D professionals’ career aspirations. The findings of this study revealed that the level of R&D professionals’ self-efficacy, organizational socialization, continuous improvement (CI) practices, and career aspirations were high. The results indicated that the three selected factors showed significant positive relationships with the R&D professionals’ career aspirations. Nevertheless, only self-efficacy and CI practices were found to be significant in explaining the variation of career aspiration. The predictor variables explained 15.5% of the variance in the R&D professionals’ career aspiration. The study concluded that R&D professionals’ self-efficacy, organizational socialization, and CI practices are important factors that determined their career aspirations. This study implied that R&D professionals must equip themselves with high level of self-efficacy, organizational socialization and CI practices to enhance their career aspirations. It is recommended that the HRD system of the GRIs need to formulate a career development programs that considers R&D professionals’ self-efficacy, promotes more learning experiences through organizational socialization and strengthens the quality improvement work-procedures. Although it had been identified that the career aspirations held by the R&D professionals are high, however, this study did not explore their career aspirations with different career stages. Therefore, additional study is necessary to delve into the stability of their career aspirations over different career stages.